2008
DOI: 10.1029/2007jc004658
|View full text |Cite
|
Sign up to set email alerts
|

Sand banks of finite amplitude

Abstract: [1] The process which leads to the appearance of sand banks in shallow seas is investigated by studying the growth of small-amplitude perturbations of the sea bottom, forced by oscillatory tidal currents. Since the analysis of field data carried out by Dyer and Huntley (1999) suggests that sand banks are likely to occur where the tidal ellipse is circular or characterized by a low ellipticity, attention is focused on small values of, where e is the ratio between minor and major axes of the tidal ellipse. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…It was also found that the modeled ridge height overestimated the observed ridge height of the Dutch Banks in the southern North Sea. Tambroni and Blondeaux (2008) carried out a weakly nonlinear stability analysis to investigate the behavior of finite-height ridges. Their method is fast, but it is only applicable for tidal currents with large ellipticity ϵ (the ratio between the minor axis and the major axis of the tidal current ellipse).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that the modeled ridge height overestimated the observed ridge height of the Dutch Banks in the southern North Sea. Tambroni and Blondeaux (2008) carried out a weakly nonlinear stability analysis to investigate the behavior of finite-height ridges. Their method is fast, but it is only applicable for tidal currents with large ellipticity ϵ (the ratio between the minor axis and the major axis of the tidal current ellipse).…”
Section: Introductionmentioning
confidence: 99%
“…Many tidal sand ridges are actually observed at locations where tidal currents are close to rectilinear (ϵ ∼ 0), for instance, in the southern North Sea (Collins et al, 1995). Furthermore, the effect of the critical bed shear stress for sand erosion on the evolution of finite-height ridges has not been considered in the above studies, except in Tambroni and Blondeaux (2008). In Yuan et al (2016), it was shown that including the critical bed shear stress for sand erosion significantly affects the characteristics of tidal sand ridges during their initial formation.…”
Section: Introductionmentioning
confidence: 99%
“…In Besio et al [5], as well as in later studies by Tambroni and Blondeaux [72], Blondeaux et al [8] and Yuan et al [91] , two additional effects are accounted for that are not present in formulation (1). The first is that transport includes a critical velocity for erosion and the second is that transport due to longitudinal and lateral bed slopes differ.…”
Section: Discussionmentioning
confidence: 99%
“…The ridges with asymmetrical profiles migrate in the flood direction (positive x-direction). Tambroni and Blondeaux [72] carried out a weakly nonlinear stability analysis to investigate the behaviour of finite-height ridges in a 2DH (depth-averaged) model. Their method is fast and yields insight into the mechanism that causes saturation of the height of the ridges, but it is only applicable for tidal currents with large ellipticity .…”
Section: Early Modelsmentioning
confidence: 99%
“…Linear stability analysis yields a preferred bedform of which the spacing and orientation are in fair agreement with those of the observed tidal sand ridges. For ridges with a finite height, nonlinear (or weakly nonlinear) models (Huthnance, 1982b;Roos et al, 2004;Tambroni and Blondeaux, 2008;Yuan et al, 2017, and references therein) were employed to investigate the behavior of these ridges. In these models, the sea level and the tidal current were kept constant in time.…”
Section: Introductionmentioning
confidence: 99%